Four Thousand Years of History at Tel Beth-Shean: An Account of the Renewed Excavations - Mazar, Amihai (The Biblical archaeologist, 1997)
From its towering command of a strategic crossroads, the steep mound of Beth-Shean beckoned excavators in the early part of this century. Returning to the site with its extended settlement history, archaeologists from the Hebrew University's Institute of Archaeology opened a large-scale project in 1989. Eight seasons of excavation have answered many of the unresolved issues, produced more precise stratigraphic and architectural definitions, and illuminated the settlement continuum and its shifting character on the tell. Of special note are the surprising finds from the Egyptian New Kingdom period when Beth-Shean served as the center of Egyptian imperial rule in the north of Canaan.